Transactional relations between caregiving stress, executive functioning, and problem behavior from early childhood to early adolescence. (18th July 2016) - Lagasse, Linda L.; Conradt, Elisabeth; Karalunas, Sarah L.; Dansereau, Lynne M.; Butner, Jonathan E.; Shankaran, Seetha; Bada, Henrietta; Bauer, Charles R.; Whitaker, Toni M.; Lester, Barry M.
Abstract: Developmental psychopathologists face the difficult task of identifying the environmental conditions that may contribute to early childhood behavior problems. Highly stressed caregivers can exacerbate behavior problems, while children with behavior problems may make parenting more difficult and increase caregiver stress. Unknown is: (a) how these transactions originate, (b) whether they persist over time to contribute to the development of problem behavior and (c) what role resilience factors, such as child executive functioning, may play in mitigating the development of problem behavior. In the present study, transactional relations between caregiving stress, executive functioning, and behavior problems were examined in a sample of 1, 388 children with prenatal drug exposures at three developmental time points: early childhood (birth to age 5), middle childhood (ages 6 to 9), and early adolescence (ages 10 to 13). Transactional relations differed between caregiving stress and internalizing versus externalizing behavior. Targeting executive functioning in evidence-based interventions for children with prenatal substance exposure who present with internalizing problems and treating caregiving psychopathology, depression, and parenting stress in early childhood may be particularly important for children presenting with internalizing behavior.